Regional odontodysplasia - D N Mehta; D Bailoor; B Patel (Wolters Kluwer Medknow Publications, 2011)
Regional odontodysplasia is an unusual developmental anomaly in which ectodermal and mesodermal tooth components are affected. We present a rare case of a developmental anomaly called regional odontodysplasia or 'ghost teeth' in a 12-year-old Indian girl. The anomaly affected right maxillary permanent teeth. The mandibular teeth were unaffected. The clinical, radiographic and histological features are reviewed. The management of affected patients is discussed.